PENGARUH METODE PEMBELAJARAN EKSPERIMEN TERHADAP PENINGKATAN KEMAMPUAN KOGNITIF IPA SISWA KELAS IV MATERI SIFAT DAN PERUBAHAN WUJUD BENDA - Anisa Rahma Salsabilah; Regina Lichteria Panjaitan; Ali Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study is the low student learning outcomes caused by conventional learning, which tends to be monotonous and teacher-centered. This study used a quantitative method with a quasi-experimental research type and a pretest-posttest control group design. The study sample consisted of two groups: an experimental group treated with experimental learning, and a control group treated with conventional learning methods. Data analysis used normality and homogeneity tests, and hypothesis testing using the Wilcoxon and Mann-Whitney tests due to the non-normal distribution of the data. The results of this study indicate that there is a difference in cognitive ability improvement between the experimental and control groups. The experimental group using the experimental learning method obtained an average N-Gain score of 0.587 (moderate category), while the control group obtained an average score of 0.389 (moderate category). The results obtained were greater in the experimental group, indicating that the experimental method was more effective than conventional learning in improving students' cognitive abilities.